Effects of weight, gender and number of pregnancies on lumbar total and segmental lordosis and low back pain - Khodadad Letafatkar; Maliheh Hadadnezhad; Hosein Arashpour; Mahdi Bakhsheshi Heris (Vesnu Publications, 2010)
Introdaction:The spine is an important part of the human skeletal system. The objective of this identify was to study the effects of weight, gender and number of pregnancies (in females) on low back pain and the lumbar total and segmental lordosis.Materials and Methods: Seventy five subjects (41 males and 34 females) aged between 18 and 62 years were randomly selected. The subjects had not any previous history of back-pain or related surgery. Lateral X-ray in standing position followed by the cobb method was used to evaluate lumbar total and segmental lordosis. Variables such as subjects age, weight, height, gender, body mass index (BMI) and number of previous pregnancies (for the females) were obtained and recorded on a data sheet. In this study, pain scores were evaluated by a pain ruler. For the statistical analysis of the date, the ANOVA, tokey post hoc test and sample t-test were applied by the meaningful statistical level of less than 0.05. Results: The amount of lumbar total lordosis was greater in females compared to the male subjects. Lumbar segmental lordosis in various parts were as follow: L1-L2 (4 in men, 6 in women), L2-L3 (8 in men, 9 in women), L3-L4 (8.7 in men, 9.5 in women), L4-L5 (12 in men, 14.6 in women), L5-S1 (23 in men, 18 in women). The degree of lumbar lordosis (upper part) was greater in obese females compare to normal weights. The number of pregnancy was in correlation with the increase in the degree of lumbar total lordosis in female subjects. Women had more pain than men. Conclusion: It can be concluded that obesity, gender, body mass index and multiple child birth have significant effects on low back pain and lumbar total and segmental lordosis. Keywords: Spine, Obesity, Lordosis, Pregnancy.Letafatkar Kh*, Hadadnezhad M1, Arashpour H MD2, Bakhsheshi Heris M3